Norma, Kode Etik dan Sanksi Akreditasi Sistem Persekolahan - Muhammad Naufal Baehaki; Ardian; Husnul Yaqin; Hilmi Mizani (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This literature review examines the role of norms, codes of ethics, and sanctions within the school accreditation system. Using a qualitative literature review approach, the study analyzes journals, books, regulations, and accreditation guidelines. The findings show that accreditation norms guide institutional behavior, codes of ethics ensure professionalism and transparency, and sanctions function as corrective measures for non-compliance. The integration of these elements strengthens the credibility, effectiveness, and sustainability of educational quality assurance. Strengthening ethical awareness and regulatory compliance remains essential for improving educational quality.